ECONMATH Current Research Trends in Economics and Mathematics - SZABÓ, Tünde; TÓTH, Vanda (Presa Universitară Clujeană, 2026)
As a first edition, on 19th September 2025, the Department of Business Administration, Sf. Gheorghe of the Faculty of Economics and Business Administration, Babeş-Bolyai University, organized the conference entitled ECONMATH - "Current Research Trends in Economics and Mathematics". The primary aim of the event was to provide a forum for inspiring and constructive discussions of current research topics in Economics and Mathematics, with the hope of finding efficient solutions to different economic and mathematical problems.